Pengembangan Terpadu City Tour Semarapura Melalui Ship Approach - Nuriawan, I Nengah Alit; Paturusi, Syamsul Alam; Sunarta, I Nyoman (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 02, Januari 2021, 2021)
The development of Semarapura City Tourism through City Tour has not been running as expected, so it has not been able to increase foreign tourist arrivals and has not been able to improve the economy of the community. The research objective was to identify integrated development of City Tour City Semarapura tourism through the SHIP Approach. This study uses a qualitative descriptive approach. Data collection methods used in this study were observation and interviews. The theory used in this study is the Tourism Area Life-Cycle, explaining the position of development of Semarapura tourism. SHIP theory (systemic, holistic, interdiciplinary, and participatory) to describe and explain how the integrated development of City Tour in Semarapura City. The integrated form of City Tour tourism in Semarapura city is carried out by designing tourism models with improvements to the previous City Tour program and designing new tour packages, with additional classes for each package. Puppet painting class, weaving class, metal craft / kepeng money making class and brown sugar making class. The development of City Tour with the addition of tourist classes will provide experience for foreign tourists who visit and have a positive impact on the economy of the community through active participation from all stakeholders. Keywords: Integrated development, Semarapura city tourism, SHIP Approach